PENDAMPINGAN PENINGKATAN PERAN PEREMPUAN DALAM MENDUKUNG KEMANDIRIAN EKONOMI RUMAH TANGGA - Hartiningsih Astuti; Joko Hadi Susilo; Izza Ahmad Utomo; Dimas Surya Atmaja; Sahra Dwi Irma Rosida (Universitas Kadiri, 2025)
This mentoring program aims to improve household economic independence by improving entrepreneurial skills and financial management for housewives who are guardians of students at the Al-Fathin Foundation, Bojonegoro. Mentoring is carried out in several stages, starting from identifying problems and potentials, providing materials to monitoring and evaluation. The results of the mentoring show that participants have increased their understanding of the concept of entrepreneurship and household financial management. Most participants have implemented simple financial records, understand budget planning and concepts in developing small businesses. The obstacles faced in this program include limited time for participants, access to business capital, and adaptation to digital technology in marketing. However, overall, this program has a positive impact on improving participants' economic skills and encouraging the formation of a more independent and economically empowered women's community.